Effect of Pb(Y1/2Nb1/2)O3 additions on thermal and electrical properties of PbZrO3 ceramics - Sukkha, Usa; Muanghlua, Rangson; Niemcharoen, Surasak; Boonchom, Banjong; Vittayakorn, Naratip (My University, 2011)
The solid solution of a (1-x)PbZrO3 - xPb(Y1/2Nb 1/2)O3 (PZ - PYN) system, with x = 0.00 - 0.08, was synthesized by the wolframite precursor method. The effects of PYN content on crystal structure, and electrical and thermal properties of PbZrO3 ceramic were investigated. The crystal structure of sintered ceramics was characterized by X-ray diffraction. The pure perovskite phase was obtained for all compositions. The transition temperatures of the AFE to PE phase become lower with PYN increase. The dielectric properties of PZ were improved by the addition of PYN. Copyright © Taylor & Francis Group, LLC.
Keywords: Antiferroelectric; Lead Yttrium Niobate; Lead Zirconate; Wolframite precursor method